THE ROLE OF TECHNOPARKS IN THE DEVELOPMENT OF INNOVATIVE INFRASTRUCTURE IN UZBEKISTAN - Umarova Zevi Adilovna (Scholar Express Journals, 2023)
In Uzbekistan, comprehensive measures are being carried out on the wide introduction of innovations in the fields of Economics, stimulation of innovative activities, especially industrial production, large-scale establishment of the activities of technoparks, transfer centers, innovation clusters, venture organizations, business incubators. Also in the country"...The Global Innovation Index defines the task of" improving the position of the Republic of Uzbekistan and entering the top-50 countries of the rating by 2030". In this regard, it is advisable to pay special attention to research in such areas as theoretical and methodological improvement of the mechanism for assessing national innovative potential, effective formation of innovative clusters on the basis of state-specific partnerships, stimulation of innovative activities of private sectors and regions by financial means, effective organization of the mechanism for their implementation.
Keywords: innovation economy; national innovation system; innovation infrastructure; technopark